Practice-based training strategy for therapist-driven prostate MR-Linac adaptive radiotherapy - Winnie Li; Jerusha Padayachee; Inmaculada Navarro; Jeff Winter; Jennifer Dang; Srinivas Raman; Vickie Kong; Alejandro Berlin; Charles Catton; Rachel Glicksman; Victor Malkov; Andrew McPartlin; et al. (Technical Innovations & Patient Support in Radiation Oncology, 2023)
Purpose: To develop a practice-based training strategy to transition from radiation oncologist to therapist-driven prostate MR-Linac adaptive radiotherapy. Methods and materials: In phase 1, 7 therapists independently contoured the prostate and organs-at-risk on T2-weighted MR images from 11 previously treated MR-Linac prostate patients. Contours were evaluated quantitatively (i.e. Dice similarity coefficient [DSC] calculated against oncologist generated online contours) and qualitatively (i.e. oncologist using a 5-point Likert scale; a score ≥ 4 was deemed a pass, a 90% pass rate was required to proceed to the next phase). Phase 2 consisted of supervised online workflow with therapists required no intervention from the oncologist on 10 total cases to advance. Phase 3 involved unsupervised therapist-driven workflow, with offline support from oncologists prior to the next fraction. Results: In phase 1, the mean DSC was 0.92 (range 0.85–0.97), and mean Likert score was 3.7 for the prostate. Five therapists did not attain a pass rate (3–5 cases with prostate contour score < 4), underwent follow-up one-on-one review, and performed contours on a further training set (n = 5). Each participant completed a median of 12 (range 10–13) cases in phase 2; of 82 cases, minor direction were required from the oncologist on 5 regarding target contouring. Radiation oncologists reviewed 179 treatment fractions in phase 3, and deemed 5 cases acceptable but with suggestions for next fraction; all other cases were accepted without suggestions. Conclusion: A training stepwise program was developed and successfully implemented to enable a therapist-driven workflow for online prostate MR-Linac adaptive radiotherapy.